(untitled) (Al-Academy, 2026)
This research presents an analytical comparison between the musical accompaniment of Iraqi songs in the 1980s and 1990s, through the analysis of two models representing each decade. The focus is on three elements: rhythm, melody, and harmony, aiming to reveal differences in musical structure, instruments, and techniques. The results show a marked development in the 1990s in terms of the multiplicity of rhythmic lines or layers, the diversity of instruments, and the use of electronic devices such as the organ with its multiple sounds and percussion instruments, as well as the application of modern recording technologies like sequencers. There was also a growing emphasis on harmony and the use of chords and their musical functions, in contrast to the simplicity of the musical texture in the 1980s and its reliance on traditional instruments and conventional methods of executing musical accompaniment. These differences reflect the impact of technological and cultural shifts on musical arrangement methods for songs and, in particular, on musical accompaniment. They also highlight the path Iraqi song has taken towards modernity and integration with contemporary global music.